ECONOMETRIC MODELING OF AGRICULTURAL PRODUCTION DEVELOPMENT - Mukhitdinov , Khudayar (THE INNOVATION ECONOMY, 2023)
In this article, the scientific theoretical basis of econometric modeling is studied. Based on the empirical modeling of the development of agricultural production in the region, conclusions and suggestions were developed.